The Rule Of Law Corrupted By Law Enforcers: a Study Of Police Misconduct - Saida Flora, Henny; Suhendar, Suhendar; Fitri Hertini, Mega; Itasari, Endah Rantau; Erwin, Erwin (UNES Law Review, 2024)
The purpose of this study was to study and know the provisions of the Police Code of Ethical Principles that are the basis for the performance of duty, to study and know the responsibility of the police for violating the Code of Ethical Principles, and to know the responsibility for the violation of the Code of Ethical Principles. According to the provisions of the Regulation of the Chief of the National Police of Indonesia No. 14 of 2011 on the Code of Ethical Principles of the National Police of Indonesia, Article 1 regarding the definition of KEPP, viz. "The Code of Ethical Principles of the POLRI, hereinafter abbreviated as KEPP, is the norms or rules that constitute the unity of ethical or philosophical foundations regarding behavior and speech in relation to things that are required, prohibited, appropriate or inappropriate to be done by members of the POLRI in the performance of the duties, powers and responsibilities of the position.